2013
DOI: 10.1159/000356405
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Cellular Cohesion in Cytology Composes a Special Subgroup of Breast Tumors - Analysis of 37 Cases

Abstract: Objective: We analyzed smears by fine needle aspiration (FNA) from 37 cases that displayed numerous dissociated cells and correlated the results with histological findings. Study Design: Between 1996 and 2005, 1,583 patients underwent breast FNA and resection. Loss of cellular cohesion was observed in 37 of these cases. Results: From the cytological findings, we classified cases into 3 groups according to cell size and shape. Type A: numerous isolated spindle cells with a necrotic background. Four cases were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…Many studies had described the cytological criteria's to diagnose medullary, medullary-like, and metaplastic carcinoma,[26] but in current study, we observed only few cases of above said malignancies; hence data were found to be insufficient for detail morphological studies of these malignancies.…”
Section: Discussioncontrasting
confidence: 59%
“…Many studies had described the cytological criteria's to diagnose medullary, medullary-like, and metaplastic carcinoma,[26] but in current study, we observed only few cases of above said malignancies; hence data were found to be insufficient for detail morphological studies of these malignancies.…”
Section: Discussioncontrasting
confidence: 59%
“…Wakasa et al [35] described a cytological subclassification for breast cytology that showed loss of cellular cohesion; for invasive lobular carcinoma, medullary carcinoma, neuroendocrine carcinoma, and solid papillary carcinoma, this criterion was present in most cases. However, cellular cohesion was not studied for the luminal phenotype of breast carcinoma yet.…”
Section: Discussionmentioning
confidence: 99%